Pengaruh Balance Exercise Terhadap Tingkat Keseimbangan Dalam Penurunan Risiko Jatuh Pada Lansia - Ni Putu Natasya Nadi Sari; Martini, Ni Made Dwi Ayu; Triana, Komang Yogi; Sari, Ayu Ratih Cempaka (Jurnal Keperawatan Muhammadiyah, 2025)
Elderly undergo a reduction in physical functions, especially in the musculoskeletal system, such as a decrease in muscle power, which affects their capacity to sustain body equilibrium and raises the likelihood of falling. Balance training can assist in enhancing balance by boosting muscle contractions and fiber strength, which consequently improves muscle power and helps maintain an upright posture, thus lowering the chances of falls. The goal of this research is to assess the effect of balance training on the balance level in reducing fall risk among the elderly. This study used a pre-experimental research design with a one-group pretest-posttest design, involving 49 respondents selected through purposive sampling. Data collection instruments included a balance level measurement sheet using the Time Up and Go Test (TUGT) and the Standard Operating Procedure (SOP) for Balance Exercise. Data analysis was conducted using the Wilcoxon Signed Rank Test. The results showed a difference in the average balance level before (pretest) performing the balance exercise, which was 21.80 seconds, compared to the average balance level after (posttest) performing the balance exercise, which was 16.27 seconds. The analysis showed a calculated z-value of -6.059, which is greater than the table z-value of 1.960, with a p-value of 0.00 (p-value < 0.05). Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted, concluding that balance exercises affect the level of balance in the elderly, thus reducing fall risk. It is recommended for the elderly to practice balance exercises regularly twice a week